Evaluasi Kepuasan Pengguna Terhadap Aplikasi Jelajah Ilmu Menggunakan HOT-Fit Model Pada MIN 1 Muara Enim - Mu'arif Rawhul Ihsan; Evi Yulianingsih (BETRIK, 2025)
This study aims to examine the influence of three main constructs Technology, Human, and Organization on the Benefit variable in the implementation of the Jelajah Ilmu application at MIN 1 Muara Enim. A quantitative approach was employed using a five-point Likert scale (1–5) questionnaire, which was completed by 95 participants consisting of teachers and students. To assess and test the relationships among variables, the analysis was conducted within the HOT-FIT framework. The findings reveal that the Technology variable, represented by the dimensions of System Quality and Information Quality, has a significant effect on System Use. However, System Quality does not show a significant impact on User Satisfaction. The Human variable, through the dimensions of Service Quality and User Satisfaction, is proven to affect System Use; nevertheless, User Satisfaction does not significantly influence Benefit. The Organization variable, represented by both Structure and Organizational Environment dimensions, demonstrates a significant effect on User Satisfaction and Benefit. Therefore, it can be concluded that Technology, Human, and Organization collectively play a crucial role in optimizing the benefits derived from the use of the Jelajah Ilmu application within the school context.